Instability Mode and Control Technology of Surrounding Rock in Composite Roof Coal Roadway under Multiple Dynamic Pressure Disturbances - Peng Wang; Nong Zhang; Jiaguang Kan; Xingliang Xu; Guangzhen Cui (Geofluids)
In view of the problems of composite roof coal roadway under multiple dynamic pressure disturbances such as strong stratification, large deformation of the roadway surrounding rock, and poor safety and reliability, this paper analyzed the deformation and instability characteristics of composite roof coal roadway under different influencing factors using numerical simulation and expounded the stress distribution pattern of composite roof coal roadway under multiple dynamic pressure disturbances. The geological conditions of gas control roadway in the 22301 working face of Tunlan coal mine are taken as examples, and this study is carried out based on the analysis of roof instability conditions of composite roof coal roadway. The progressive crack development characteristics in composite roof coal roadway and the instability failure mode of surrounding rock under multiple dynamic pressure disturbances were revealed, and the control mechanism and support scheme were put forward. According to the result, it is difficult to form a stable bearing rock beam due to the occurrence characteristics of the weak interlayer of the composite roof. The deflection of the roadway roof and the extent of the plastic zone are negatively correlated with the distance from the soft rock layer to the roadway but positively correlated with the thickness of the soft rock layer. As the lateral pressure coefficient λ increases, the plastic zone of the roadway surrounding rock first decreases and then increases. With the increasing influence of dynamic pressure, the coal roadway with composite roof suffers from greater damage under the superposition of high ground stress, lateral abutment pressure, and advance abutment pressure, which is characterized by significant zonal failure of the roof and asymmetric failure of surrounding rock. The control method of high-strength thick anchorage+differential support can construct the thick layer stable rock beam of the roof and equivalent support of the side, realizing continuous stress transfer and geometrically coordinated deformation. The support scheme was finally applied to the on-site industrial test, and the mine pressure monitoring results showed that the deformation of the roadway surrounding rock was effectively controlled under the new support scheme.